Blockchain-Based E-Certificate System: Secure and Transparent Credential Management - Chotijah, Umi; Teguh Prayudha, Ilham; Rifki, Achmad (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study explores the development of a blockchain-based e-certificate system designed for secure and transparent credential management at the Muhammadiyah University of Gresik. Leveraging private blockchain technology, the system addresses the challenges of certificate forgery and unauthorized alterations by ensuring data immutability and integrity. Through the implementation of a distributed ledger, the platform facilitates seamless issuance, verification, and storage of e-certificates. The methodology encompasses system design using the waterfall model, including stages of requirement analysis, system design, implementation, integration, and testing. Smart contracts are utilized to automate certificate verification processes, enhancing efficiency and reliability. The research findings demonstrate that the blockchain-based system not only secures the certification process but also streamlines operations by eliminating intermediaries. This innovative approach holds promise for broader applications in academic institutions and beyond, offering a scalable solution for secure document management. Future studies may expand its applicability across diverse industries.